2021
DOI: 10.1007/s10869-021-09757-0
|View full text |Cite|
|
Sign up to set email alerts
|

Organizational Benefits of Onboarding Contingent Workers: an Anchoring Model Approach

Abstract: Organizations rarely invest in contingent employees, at least relative to the human resources efforts commonly afforded to permanent workers -but should they? Traditional social exchange theory suggests that motivation and loyalty should be difficult to cultivate in short-term, fixed-term relationships like contingent employment. However, a novel social exchange model (i.e., the anchoring model) suggests that socioemotional exchange relationships can develop quickly in response to highly salient "anchoring eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Just how many platform workers depend on gigs for their primary earning remains an open question. Estimates range from 22% (Schor, 2020) to 56% of gig workers (Smith, 2016). It would be useful to understand the types of individuals who take gigs with high dependence, as this may allow us to develop tools and societal safeguards for protecting vulnerable workers.…”
Section: Worker Adaptation To Algorithmic Management: Autonomy and De...mentioning
confidence: 99%
See 1 more Smart Citation
“…Just how many platform workers depend on gigs for their primary earning remains an open question. Estimates range from 22% (Schor, 2020) to 56% of gig workers (Smith, 2016). It would be useful to understand the types of individuals who take gigs with high dependence, as this may allow us to develop tools and societal safeguards for protecting vulnerable workers.…”
Section: Worker Adaptation To Algorithmic Management: Autonomy and De...mentioning
confidence: 99%
“…There are established measures for assessing the utility of training and development activities that could be applied to investigate when training opportunities for gig workers could be cost effective, such as low-cost training or training for workers with reoccurring gig contracts in a single firm (e.g., Carretero-Gómez & Caberra, 2015; Chochard & Davoine, 2011). For example, Smith et al (2022) find that effective onboarding—a training-like human resources practice that helps newcomers adapt to their work and organization culture—among contingent workers actually increases their task performance and intent to return. Likewise, there may also be ways to avoid legal challenges, such as through better contracting or perhaps restricting some developmental programs to gig workers.…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
“…Moreover, globalization has accelerated and increased the number of people entering and exiting organizations. Organizations, consequently, benefit when new members reach their performance potential quickly and remain in the organization performing efficaciously (Smith et al , 2021). Postolache (2017) reported that new employees encountering effective organizational socialization were 58% more likely to work for the organization in excess of three years.…”
mentioning
confidence: 99%
“…Studies have illustrated that employee-related outcomes are related to the employee's experience in onboarding; these include job performance (Ashford & Blac, 1996;Bauer et al, 2007;Caldwell & Peters, 2018;Saks & Gruman, 2018;Smith et al, 2021;Wiseman et al, 2022), turnover intention (Bauer et al, 2007;Beaver & Hutchings, 2005;Gupta et al, 2018;Meyer & Bartels, 2017;Narayansany & Isa, 2021;Pratiwi et al, 2018;Smith et al, 2021), employee satisfaction (Ashford & Black, 1996;Bauer et al, 2007;Bauer & Erdogan, 2011;Cable et al, 2013), employee motivation and engagement (Cable et al, 2013;Chillakuri, 2020;Jeske & Olson, 2021;Mahmood et al, 2022;Petrilli et al, 2022;Saks & Gruman, 2018), burnout (Frögéi et al, 2022, organization-based self-esteem (Frögéli et al, 2022;Gardner et al, 2021), and organizational commitment (Beaver & Hutchings, 2005;Meyer & Bartels, 2017;Sharma & Stol, 2020). Additionally, research has explored how locus of control and work-related self-efficacy is impacted by onboarding, as well as the intervening role these characteristics play on the relationship between onboarding and other outcomes (Chen et al, 2016;Domene, 2012;Gangai et al, 2016;Gupta et al, 2018;Judge & Bono, 2001;König et al, 2010;…”
Section: Employee Outcomesmentioning
confidence: 99%
“…Research has found that new employee onboarding, when effective, is correlated to an employee's job performance (Ashforth et al, 2007;Bauer et al, 2007;Smith et al, 2021;Wiseman et al, 2022). For example, in their study of newly onboarded salespeople at a furniture retailer chain, Wiseman et al (2022) In addition to job performance, research has found that turnover intention and organizational commitment are correlated with onboarding (Beaver & Hutchings, 2005;Gupta et al, 2018;Meyer & Bartels, 2017;Narayansany & Isa, 2021;Sharma & Stol, 2020;Smith et al, 2021).…”
Section: Employee Outcomesmentioning
confidence: 99%